2016
DOI: 10.1021/acs.jpcc.6b11651
|View full text |Cite
|
Sign up to set email alerts
|

Watching the Vibration and Cooling of Ultrathin Gold Nanotriangles by Ultrafast X-ray Diffraction

Abstract: We study the vibrations of ultrathin gold nanotriangles upon optical excitation of the electron gas by ultrafast X-ray diffraction. We quantitatively measure the strain evolution in these highly asymmetric nano-objects, providing a direct estimation of the amplitude and phase of the excited vibrational motion. The maximal strain value is well reproduced by calculations addressing pump absorption by the nanotriangles and their resulting thermal expansion. The amplitude and phase of the out-of-plane vibration mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…The lattice strains ε Ni,Au ( t ) = −cot( ϑ ( t ))Δ ϑ ( t ) perpendicular to the sample surface are directly retrieved from the time-resolved Bragg-peak positions ϑ ( t ) (Fig. 2b, c ) 58 39 , 40 . These UXRD data were recorded at our laser-driven plasma X-ray source at the University of Potsdam, that emits 200 fs X-ray pulses with a photon energy of 8 keV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lattice strains ε Ni,Au ( t ) = −cot( ϑ ( t ))Δ ϑ ( t ) perpendicular to the sample surface are directly retrieved from the time-resolved Bragg-peak positions ϑ ( t ) (Fig. 2b, c ) 58 39 , 40 . These UXRD data were recorded at our laser-driven plasma X-ray source at the University of Potsdam, that emits 200 fs X-ray pulses with a photon energy of 8 keV.…”
Section: Methodsmentioning
confidence: 99%
“…While free electron laser facilities are in very high demand, an alternative is offered by laser-based plasma sources of femtosecond X-rays 37 , 38 , which lack the coherence and high flux of a free electron laser but are fully adequate for UXRD measurements 6 , 39 , 40 . As an example, a recent experiment on 6 nm thick Au nanotriangles 39 confirmed the = 5 ps electron–phonon equilibration time generally accepted for high fluence excitation of Au 3 , 6 , 41 , 42 . For similar fluences ultrafast electron diffraction reported = 0.75 to 1 ps for Ni thin films between room temperature and Curie temperature T C 7 , 43 .…”
Section: Introductionmentioning
confidence: 99%
“…79% of the nanoplatelets (including hexagonal and triangular nanoprisms) are long-term stable AOT-coated AuNTs with an average edge length of 175 AE 17 nm. 8 A special feature of the ultrathin nanoplatelets with a thickness of 7.5 AE 1 nm, calculated by different methods, i.e., X-ray reectivity, TEM tomography, 46 SAXS measurements, 30 and veried in ultrafast X-ray diffraction experiments, 47 is their long-term-stability up to a laser uence of 2.9 mJ cm À2 , 47 and their ability to form monolayers. 8,31 In the following we call these ultrathin nanoplatelets AuNTs, because of the fact that 79% of the platelets are triangularlyshaped.…”
Section: Aunts Synthesismentioning
confidence: 99%
“…This is in good agreement with EDX measurements from Atta et al, where the authors have found metallic silver at both side walls of the spike, 10 as well our own EDX-line scan across a gold nanostar-spike, synthesized in concentrated aqueous AOT solution. 47 The absence of the absorption peak around 650 AE 150 nm in the synthesis of SAuNTs in presence of AgNO 3 is related to the fact that the whole amount of Au 3+ ions is required for the formation of the spikes, meaning that no more precursor salt is available for making gold nanoparticles in solution.…”
Section: Saunt Formation In Presence Of Agnomentioning
confidence: 99%
“…A novelty of the AOT-stabilized AuNTs is their long-time stability and the possibility of surface modification in the AOT-bilayer. Ultrafast X-ray diffraction measurements have shown that AOT-stabilized AuNTs stay intact at a base temperature of 24 K with a pump wavelength of 400 nm and a fluence of 2.9 mJ/cm 2 [45]. Ultrafast X-ray diffraction induces a primary oscillatory motion with a single damped out-of-plane breathing mode with a period of 3.6 ps [45].…”
Section: Discussionmentioning
confidence: 99%